Produksi Serasah Mangrove di Biangkuk, Kabupaten Merauke - Saleky, Dandi; Sianturi, Reny (AGRICOLA, 2020)
Mangroves are plants that live in tidal or interface areas between terrestrial and marine ecosystems in tropical and subtropical regions. Mangrove ecosystem is one of the coastal ecosystems that have a very important role, especially for organisms, namely as a supplier of nutrients produced by mangrove litter. An observation regarding litter productivity is still limited in Papua, especially in the city of Merauke. The method used in this study is the transect method, using 3 (three) transects. Mangrove litter is taken by using a litter trap container placed under the mangrove tree. The results obtained from litter production in each transect are as follows transect 1 of 167.8 g/m²/Month, Transect 2 of 65.4 g/m²/Month, and Transect 60 g/m²/Month while density mangrove in each transect 1 transect has a higher tree density value of 65 Ind/ m² while in Transect 2 it has a total litter production of 32 Ind / m² and the mangrove density value in Transect 3 is lower compared to stations 1 and 2 which are 25 Ind/m².